Giving the right direction: Predictive action cues during an attentional task reduce prejudice. (September 2021) - Capellini, Roberta; Sacchi, Simona
The current work aims to investigate if social cueing during an attentional task is likely to influence prejudice. In three studies we adopted a Posner-like task whereby participants observed an outgroup (vs ingroup) member performing a reach-to-grasp movement. The individual's action, oriented rightward or leftward toward an object, preceded a peripheral target stimulus requiring a simple categorization response. The action direction could be congruent or incongruent with target location. Unbeknownst to the participants, the action direction predicted the target location with different validities. We measured the identification with the ingroup (i.e., Italians) and the prejudice toward the outgroup (i.e., Iraqi). Results showed that, for highly identified participants, explicit prejudice toward Arabs was lower after predictive-congruent social cues provided by an outgroup member than after predictive-incongruent cues. Thus, these findings suggest that positive experience with an outgroup member, even when subtle, might be effective in changing attitudes toward the entire social category.